Portraits of Creation - Chiramattel, Joseph (Journal of Dharma, 1992)
Howard J. Van Till, Robert E. Snow, John H. Stek and Davis A. Young, Portraits of Creation. Grand Rapids, Michigan: William B. Eerdmans Publishing Company, pp. X + 283